ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VIII PADA MATERI FUNGSI DI SMPN 5 SEATAP MORI ATAS DITINJAU DARI GENDER: Analysis Of Creative Thinking Ability Of Grade Viii Students On Function Material At SMPN 5 Seatap Mori Atas In Terms Of Gender - Lario, Yovita Cicilia; M., Bakri; Sukayasa, Sukayasa; Nurhayadi, Nurhayadi (Universitas Tadulako, 2024)
This study aims to analyze the creative thinking ability of grade VIII students at the junior high school level in Upper Mori. This research was conducted at SMPN 5 Seatap Mori Atas in the 2023/2024 school year. The method used in this research is descriptive qualitative method. Data collection techniques were obtained using test techniques, namely tests of students' creative thinking abilities in the form of description questions on mathematics material with indicators of fluency, flexibility, originality and elaboration. The results of this study indicate that LKT subjects and PRT subjects fulfill four indicators of creative thinking, namely fluency, flexibility, originality and elaboration.